(untitled) (Architecture Image Studies, 2025)
This study offers a comprehensive examination of the architectural, artistic, and interior design characteristics of Albanian towers in Kosovo, with particular focus on those located in the Dukagjini Plain. Through an interdisciplinary approach that incorporates fieldwork, historical documentation, and visual analysis, the research explores how these fortified residential structures fulfill both utilitarian and symbolic functions. Key aspects such as structural composition, construction materials, ornamental features, spatial organization, and decorative motifs are analyzed in relation to their historical, cultural, and aesthetic significance. The findings reveal a unique synthesis between Albanian vernacular craftsmanship and Ottoman stylistic influences, positioning the towers as expressions of identity, social status, and artistic heritage. Special attention is given to interior elements such as the men’s guest room (oda e burrave), wooden ceilings, carved doors, symbolic carpets, and semi-circular arches—each functioning not only as architectural components but also as carriers of philosophical meaning and cultural continuity. Ultimately, the towers are presented as architectural embodiments of Albanian memory, where form, material, and symbolism converge into a distinct narrative of heritage.